2013
DOI: 10.1097/tp.0b013e318282ba83
|View full text |Cite
|
Sign up to set email alerts
|

Donor and Recipient BKV-Specific IgG Antibody and Posttransplantation BKV Infection

Abstract: BKV serostatus can be used to risk stratify patients for posttransplantation infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 21 publications
4
47
1
Order By: Relevance
“…showed that the cumulative proportion of subjects BKV viremia free in the first year posttransplant was significantly decreased if the pre-implantation graft biopsy, preservation and washing solutions contained BKV DNA (12). High BKV-specific antibody titers in donors (possibly representing recent BKV exposure / higher graft load) and detection of BKV infection within 5 days of transplantation are risk factors for BKV nephropathy in kidney recipients (13). Therefore, the association of donor BKV replication and posttransplant recipient BKV viremia is likely due to tropism of BKV for the kidney and the high BKV antibody prevalence in healthy adult (14, 15) kidney donors.…”
Section: Discussionmentioning
confidence: 99%
“…showed that the cumulative proportion of subjects BKV viremia free in the first year posttransplant was significantly decreased if the pre-implantation graft biopsy, preservation and washing solutions contained BKV DNA (12). High BKV-specific antibody titers in donors (possibly representing recent BKV exposure / higher graft load) and detection of BKV infection within 5 days of transplantation are risk factors for BKV nephropathy in kidney recipients (13). Therefore, the association of donor BKV replication and posttransplant recipient BKV viremia is likely due to tropism of BKV for the kidney and the high BKV antibody prevalence in healthy adult (14, 15) kidney donors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in this study no predictive value of BKPyV serology of the recipient’s pre-transplant was found. Yet others have shown that high BKPyV-IgG titers in the donor and low BKPyV-IgG titers in the recipient, have a negative effect on the BKPyV infection post transplantation [29–31]. …”
Section: Discussionmentioning
confidence: 99%
“…However, another group found a higher risk for BK viremia in seronegative recipients who received a kidney from a seropositive donor. 94 These discrepancies may be accounted by variability in the assays used to detect BK-specific antibodies and quantitative differences in anti-BK antibody titers. It was previously shown that viremic patients had a lower antibody level pretransplant than those who never developed BK viremia.…”
Section: Qualitative and Quantitative Serostatusmentioning
confidence: 99%